Influence Of Knowledge Sharing, Work Environment And Motivation On Teacher Performance Mediated By Job Satisfaction SMK Teacher In Malang City - ABHA, Afifuddin; YAHYA, Mohammad; SETYOBUDI, Haris (Journal of Tourism Economics and Policy, 2021)
The purpose of the study was to determine the effect of knowledge sharing, work environment and motivation on teacher job satisfaction, to determine the effect of knowledge sharing, work environment and motivation on teacher performance, to determine the effect of teacher job satisfaction on teacher performance, to determine the effect of knowledge sharing, work environment and motivation on teacher performance. teacher performance mediated by teacher job satisfaction. The research population was 1,156 vocational high school teachers, with a research sample of 200 teachers as respondents. The research design is explanatory research, with a quantitative approach. The data analysis technique used Structural Equation Modeling (SEM) with AMOS 23 and SPSS 21 software. The results showed that knowledge sharing, work environment, and motivation had an effect on teacher job satisfaction.